A survey of records management practices in selected colleges and universities in Quezon City and Manila - Granda, Yolanda Canlas; Hidalgo, Namnama P.; Nivera, Pat I. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1981)
The study is intended primarily to find out the existing practices, programs, conditions, and problems of records operations in eleven colleges and universities in Quezon City and Manila and to propose necessary measures towards their improvements. It was carried out to respond to the expressed needs of archivists that the development of a comprehensive archives requires the support of an efficient and cost-effective records management program.
The institutions covered in the study include those which have archival programs and all state colleges and universities which do not have such programs but are interested in developing one. The institutions with archival programs are Ateneo de Manila University, Centro Escolar University, Lyceum of the Philippines, Maryknoll College, Philippine Women's University, University of Santo Tomas, and University of the Philippines. The state institutions which do not have archival programs but hope to develop one are Pamantasan ng Lungsod ng Maynila, Philippine Normal College, Polytechnic University of the Philippines, and Technological University of the Philippines.
Questionnaires, interviews, visits, observations, and analyses of documentary sources were employed to gather data on the three phases of records management, namely: records maintenance and control, records disposition, and records creation.
The findings and problems are enumerated below under each aspect of records management. Records Maintenance and Control: 1) No definite unit to initiate, implement, and coordinate records management activities; 2) Dearth of regular records personnel; 3) No definite policies and standard procedures; 4) Lack of space and equipment for storage; 5) Deficiency in mail operations; 6) Absence of authority to coordinate centralized or decentralized files; 7) No uniformity and standardization of classification and filing system; and 8) Ineffective control of files. Records Disposition: 1) No guidelines on records inventory and appraisal; 2) Unscheduled records; 3) Inadequate plan and system of records transfer to depositories; 4) Inadequate system of records disposal; and 5) Poor records preservation. Records Creation: 1) Lack of policies and standard procedures governing the creation and control of correspondence, forms, reports, directives, and special types of records such as maps, charts, drawings, photographs, sound recordings, and films; 2) Limited use of micrographics.
Recommendations towards an improved records management program are provided for each area of records activity.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Records management; Universities and colleges -- Philippines -- Manila; Universities and colleges -- Philippines -- Quezon City